Attitudes des élèves en mathématiques : quand le contexte fait ressortir l’importance des émotions - Genoud, Philippe A. (La Revue LEeE, 2022)
This article aims to gain a better understanding of how students' attitudes towards mathematical problem solving operate. More specifically, it examines the extent to which these attitudes may play a different role depending on the context. To this end, we submitted two very similar golden rule math problems to 94 students in grade 10, once in the mathematics class and once in the French class. Our results are presented in three parts. First, in line with much other research, we highlight the significant gender differences in attitudes, with girls developing more negative and potentially deleterious attitudes to their learning. Second, we find significant links between various dimensions of attitudes (cognitive, affective and behavioral) and students' academic achievement in mathematics. Finally, our analyses underline that in the context of the mathematics course, it is mainly anxiety that disturbs the success of the exercise, whereas the resolution of a very similar exercise is favored by positive emotions when it is inserted in a French worksheet. This suggests that students activate certain attitudes depending on the context – and in particular certain affects – which will have an impact on their performance. Such a result thus underlines the importance of emotions in learning and the way in which the context can induce them.
Number: 5
Keywords: contexte